Kewenangan Bea dan Cukai Dalam Penegakan Hukum Penyelundupan Ekspor di Indonesia - Casnoyo Casnoyo; Zaenal Arifin; Kukuh Sudarmanto; Cita Tsaabiethah Agustria Sasti (JURNAL USM LAW REVIEW, 2025)
This study analyzes the authority of Customs and Excise Officials in enforcing export smuggling laws in Indonesia and examines factors affecting the effectiveness of Article 102A of the Customs Law. Using a normative-empirical legal research method, this study combines statutory analysis with empirical data from law enforcement practices at the Tanjung Emas Customs and Excise Office. The findings indicate that enforcement of export smuggling provisions remains suboptimal, as many violations are redirected to other legal provisions with lighter sanctions. Key obstacles include high inspection costs for export goods already loaded onto vessels, social pressure from other exporters and transport operators, and the discretionary use of authority in response to complex field conditions. These factors weaken legal certainty and the deterrent effect of export smuggling law enforcement. This study argues that although administrative discretion is legally justified, it requires clearer boundaries and stronger institutional support to enhance enforcement effectiveness. The novelty of this research lies in its analysis of the relationship between the formulation of Article 102A and the practical limitations faced by Customs authorities, leading to recommendations for clearer discretionary guidelines, improved inter-unit coordination, and strengthened institutional capacity.   Penelitian ini menganalisis kewenangan Pejabat Bea dan Cukai dalam penegakan hukum terhadap tindak pidana penyelundupan di bidang ekspor serta faktor-faktor yang memengaruhi efektivitas penerapan Pasal 102A Undang-Undang Kepabeanan. Penelitian menggunakan metode hukum normatif-empiris dengan mengombinasikan analisis peraturan perundang-undangan dan data empiris dari praktik penegakan hukum di KPPBC Tipe Madya Pabean Tanjung Emas. Hasil penelitian menunjukkan bahwa penegakan hukum penyelundupan ekspor belum optimal karena banyak pelanggaran dialihkan ke ketentuan lain dengan sanksi yang lebih ringan. Kendala utama meliputi tingginya biaya pemeriksaan barang ekspor yang telah dimuat di atas sarana pengangkut, tekanan sosial dari eksportir lain dan pemilik sarana pengangkut, serta penggunaan diskresi administratif dalam menghadapi kompleksitas kondisi lapangan. Kondisi ini berdampak pada lemahnya kepastian hukum dan daya cegah penegakan hukum penyelundupan ekspor. Penelitian ini menegaskan bahwa penggunaan diskresi perlu dibatasi secara jelas dan didukung penguatan kelembagaan. Kebaruan penelitian terletak pada analisis keterkaitan antara rumusan Pasal 102A dan keterbatasan kewenangan Bea dan Cukai dalam praktik penegakan hukum, serta rekomendasi penguatan pedoman diskresi dan koordinasi penegakan hukum.